The Systematic Literature Review: The Effectiveness Of Implementing The Pancasila Student Profile In The Independent Curriculum And Its Implications For Students’ Character Development - Fikrotussholihah, Fitri (International Conference on Elementary Education, 2024)
In the 21st century, there are many problems in the world of education that are complex, unstable, and uncertain. One of the problems and challenges faced is the increasingly widespread moral degradation which is triggering the decline in the character of Indonesian students today. This problem is a shared responsibility within the education unit, there needs to be policy updates so that students’ character can be as expected. Character education in the curriculum that applies in Indonesia is always the main point that needs attention. Character education becomes a fortress for students to avoid phenomena and problems that occur in the students’ environment. In the proposed Independent Curriculum, the Ministry of Education and Culture has confirmed 6 dimensions of the Pancasila Student Profile. The launch of these 6 dimensions shows the characteristics that students at all levels of education must have. This research aims to conduct a literature study regarding the effectiveness of implementing the Pancasila student profile in the independent curriculum and its implications for developing students’ character. The research method used to carry out this research is the Systematic Literature Review method. Data was collected by reviewing publications on implementing the Pancasila Student Profile and the implications for character development. This research found that implementing the Pancasila Student Profile can develop students’ character by applying it in the school, family, and community environment.